Cultural Aspects of Employer Branding - Werenowska, Agnieszka; Drab, Małgorzata (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
The article presents the results of the research carried out among students coming from the UK, Ukraine, and Turkey. Surveys were conducted in 2015 amongst 105 coming students from: of Great Britain (34 persons), of Ukraine (40 persons), of Turkey (34 persons). The study aimed to show the relationship between the culture of these nations and the employer branding. The results showed the existence of relationships between cultural assumptions and factors influencing the choice of taking up employment by foreign students.